2001
DOI: 10.1152/ajpheart.2001.281.3.h1057
|View full text |Cite
|
Sign up to set email alerts
|

KVα1 channels in murine arterioles: differential cellular expression and regulation of diameter

Abstract: The primary objectives of this study were to reveal cell-specific expression patterns and functions of voltage-gated K(+) channel (K(V)alpha1) subunits in precapillary arterioles of the murine cerebral circulation. K(V)alpha1 were detected using peptide-specific antibodies in immunofluorescence and Western blotting assays. K(V)1.2 was localized almost exclusively to endothelial cells, whereas K(V)1.5 was discretely localized to the nerves and nerve terminals that innervate the arterioles. K(V)1.5 also localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 42 publications
7
70
1
Order By: Relevance
“…antibody was able to detect protein of the predicted mass in mesenteric artery samples. Similar negative findings for Kv1.5 expression in vascular tissue have been reported and extensively discussed by Cheong et al (5). However, Li et al (22) recently observed Kv1.5 expression in left coronary myocytes.…”
supporting
confidence: 86%
“…antibody was able to detect protein of the predicted mass in mesenteric artery samples. Similar negative findings for Kv1.5 expression in vascular tissue have been reported and extensively discussed by Cheong et al (5). However, Li et al (22) recently observed Kv1.5 expression in left coronary myocytes.…”
supporting
confidence: 86%
“…This reflects tissue differences in expression of K V 1 channels subtypes. In our study, margatoxin used in a concentration (10 nM) sufficient to block K V 1.1, K V 1.2, K V 1.3, and K V 1.6 channels abolished resveratrol-induced relaxation, suggesting that those channels might be included in the mechanism of resveratrol-induced endothelium-independent vasodilatation of HIMA (28,29). However, the fact that charybdotoxin, a potent blocker of K V 1.2 and K V 1.3 channels, did not reproduce the effect of margatoxin suggests that K V 1.1 and / or K V 1.6 channels may be the relevant target.…”
Section: +mentioning
confidence: 60%
“…This peptide is a highly selective inhibitor of the K V 1 channels, especially 1.1, 1.2, 1.3, and 1.6 subtypes, but displays no affinity for the mammalian BK Ca channel (28,29). K V 1.2 and K V 1.3 channels were identified in vascular smooth muscle cell of rat mesenteric artery; K V 1.1 and K V 1.6 channels were detected in smooth muscle cells of rat aorta and rat pulmonary artery, but not in smooth muscle cells of mesenteric artery (30,31).…”
Section: +mentioning
confidence: 99%
“…First, Kv1.3 is minimally expressed in normal blood vessels (45)(46)(47), and only after vascular injury does its expression increase in proliferating vascular smooth muscle cells (48)(49)(50). Second, K v channel blockers would cause vasoconstriction, not vasodilation (51). Third, ShK-186 does not alter heart rate parameters or blood pressure in chronically treated rats (20), indicating that vascular changes, if any, are not sufficient to cause BAT-mediated thermogenesis.…”
Section: Discussionmentioning
confidence: 99%